A Review, Analysis, and Roadmap to Support the Short-Term and Long-Term Sustainability of the European Crafts Sector - Nikolaos Partarakis; Xenophon Zabulis; Carlo Meghini; Arnaud Dubois; Ines Moreno; Chistodoulos Ringas; Aikaterini Ziova; Danai Kaplanidi; David Arnaud; Noël Crescenzo; Patricia Hee; Juan José Ortega; et al. (Heritage)
This publication highlights the strategic combination of the preservation of heritage and innovation for supporting the sustainability of traditional crafts in Europe. Demonstrating both challenges and opportunities faced by artisans, there is a need to balance cultural authenticity and the pressures of current markets and environmental imperatives. The research has explored interventions at three levels of craft practice, education, and training and recommends practical directions on short- and long-term bases. Key findings include new materials and technologies to revitalize crafts, the integration of digital tools in education, and cross-border collaboration, which are considered vital for enhancing the visibility and viability of traditional crafts. The circular economy principles and eco-certifications emerge as key to aligning traditional crafts with global sustainability goals. The analysis also highlights cultural policies and funding mechanisms as a means of encouraging innovation and promoting the resilience of the craft sector. The publication, by weaving together case studies, policy analysis, and strategic recommendations, provides a comprehensive roadmap for stakeholders—from artisans and educators to policymakers and researchers—to ensure that the legacy and relevance of Europe’s rich craft heritage continue.